Dynamic Response of a Single-Layer Reticulated Dome during Aircraft Impact Based on S-J Modeling Method - Li Lin; Bo Huang; Yunhui Sun; Yu Zhu; Duozhi Wang (Shock and Vibration)
In previous numerical models developed for the impact dynamic responses of reticulated domes, mostly BEAM 161 elements and piecewise linear plastic material model have been employed and spherical joints have been simplified as intersection points of beams, which is called the B-P method. The B-P method can be employed in studying the dynamic responses of reticulated shells under low- to moderate-speed impacts with no obvious temperature effect. However, the analysis of the dynamic responses of reticulated shells under moderate- and high-speed impacts of missiles and other aircraft using this method had errors because it could not take into account the temperature effect. To accurately describe the mechanical responses of reticulated shells under aircraft impacts, the Johnson–Cook material model considering temperature effect with corresponding SHELL 163 element was selected for determining the members of the numerical model and the shell element was used to establish the spherical joints of reticulated shells; the whole process was called the S-J modeling method. This modeling method was capable of considering the effects of high strain rates, high temperatures, large strains, stress state change, and loading history. S-J and B-P methods were used to model the reticulated shell structures. Comparing the numerical analysis results of the drop hammer impact of the two developed methods with experimental results verified the accuracy of the S-J modeling method. In addition, based on the results obtained from the S-J modeling method and LS-DYNA finite element analysis software, a numerical model was established for small aircraft impact reticulated shells and the failure modes and dynamic responses of reticulated shell structures under aircraft impacts were studied. In terms of energy analysis, it was found that the effects of roof plates, spherical joints, and temperature softening could not be ignored in such studies.